Concurrent hysterectomy and umbilical hernia repair via transvaginal notes among morbidly obese patients - Mehmet Mustafa Altintas; Betul Kuru; Hasan Fehmi Küçük; Selcuk Kaya; Emre Mat; Ayhan Cevik (IMR Press, 2022)
Background: Umbilical hernias are especially common along with overweight, multiparous women. Laparoscopic hernia repair is preferred due to many advantages. On the other hand, the risk of trocar site hernia is disadvantageous. Trocars do not go through the abdominal wall via transvaginal natural orifice transluminal endoscopic surgery (V-NOTES). We investigate the V-NOTES hysterectomy and concomitant umbilical hernia repairment feasibility and outcomes. Methods: Six morbidly obese patients underwent V-NOTES hysterectomy and concurrent umbilical hernia repair between April 2020 and January 2021. Demographic features of patients, operating time, hernia size, complications, hospitalization time, recurrence of the hernia, visual analog scale (VAS) at 6th, 12th, and 24th hours, first, fourth, 12th weeks, and sixth months were recorded. Results: The average age of patients was 47.667 ± 2.422 (45-52). Mean body mass index (BMI), hernia and operating time size were 44.367 ± 3.217 kg/m2 (40.3-48.5), 6.167 ± 1.722 cm (4-9) and 88 ± 12.791 minutes (75-110), respectively. Intraoperative complications did not occur. Seroma was detected in one patient(16.6%). In six month follow-up period, we did not establish a diagnosis of hernia recurrence and postoperative chronic pain. Conclusion: Our study offers a novel perspective on V-NOTES umbilical hernia repair and hysterectomy in morbidly obese patients. According to our study, performing V-NOTES umbilical hernia repairment in a risky patient population is feasible and has promising outcomes.